2022
DOI: 10.3389/fenvs.2022.1013583
|View full text |Cite
|
Sign up to set email alerts
|

Optimized flood control for the Three Gorges Reservoir considering evolving flood propagation trends in the Jingjiang Reach of the Yangtze River

Abstract: The main objective for the Three Gorges Reservoir is to help control floods and to protect the Jingjiang and Chenglingji regions in the middle reach of the Yangtze River. Hydrological measurements have demonstrated that the character of flood propagation in the Jingjiang Reach has changed significantly since the Three Gorges Reservoir became operational, meaning that flood control management must be modified accordingly. To explore the effective flood control management, a hydraulic model was developed to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, floods occur frequently in the Yangtze River basin, threatening the survival of human beings and causing extensive damage to the environment [4][5][6]. In order to achieve sustainable development of the Yangtze River, the Three Gorges Project was initially designed and built upstream to manage flood events more effectively and alleviate downstream flooding [7,8]. It has played a critical role in reducing the risk of flooding in the downstream areas of the Yangtze River, protecting millions of people and their properties from the devastating effects of floods [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, floods occur frequently in the Yangtze River basin, threatening the survival of human beings and causing extensive damage to the environment [4][5][6]. In order to achieve sustainable development of the Yangtze River, the Three Gorges Project was initially designed and built upstream to manage flood events more effectively and alleviate downstream flooding [7,8]. It has played a critical role in reducing the risk of flooding in the downstream areas of the Yangtze River, protecting millions of people and their properties from the devastating effects of floods [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have confirmed the feasibility of ecological operation, but most of the current ecological operations have the characteristic of "high-flow-rate discharge in the flood period" (Lan et al, 2022). With the increase in ecological protection awareness, the fulfillment of ecological demand at a high level has become an important goal (Niu et al, 2021), and ecological operation has expanded from the guarantee of ecological base flow of a single section to considering the ecological water demand of the area downstream (Tsai et al, 2015;Zeng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%